Perumusan Alternatif Strategi Pengembangan Pegawai Pada Komisi Pemberantasan Korupsi R - Krisnaningsih Krisnaningsih; Luki Karunia (Sekolah Pascasarjana Perbanas Jakarta, 2019)
The writing of this research is conducted to obtain internal and external factor evaluation formulation which include strength, weakness, threat and opportunity, implements internal and external factor strategy into SWOT matrix and Internal External (IE) matrix and evaluates the result of strategy that have been obtained by using Quantitative Strategic Planning Matrix (QSPM) to find alternative strategies that best fit for the needs of employee development at the Corruption Eradication Commission (KPK). The method used in this research is descriptive qualitative. Data collection techniques are conducted through personal interviews, FGDs, documentation and document analysis. The results obtained by using EFE Matrix interpreted that the Corruption Eradication Commission (KPK) has been considered capable of managing and having a good strategy in exploiting the existing opportunities and to minimize the risk of external threats. the results obtained by using the IFE Matrix interpreted that the Corruption Eradication Commission (KPK) already be considered capable of managing and have a good strategy in maximizing its strength and improve its weaknesses. Employee development of Corruption Eradication Commission (KPK) in the SWOT analysis staff development on the Corruption Eradication Commission is in quadrant II (positive and negative), this position signifies a strong organization face a great threat. In the IE matrix obtained EFE means the position of Corruption Eradication Commission (KPK) employee development is between quadrant I and II is growing and building stage. In the QSPM matrix the alternative strategy obtained is a Strategy on alternative two, namely a strategy to create, improve and modify employee development programs.